2002
DOI: 10.1038/modpathol.3880543
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody D2-40, a New Marker of Lymphatic Endothelium, Reacts with Kaposi's Sarcoma and a Subset of Angiosarcomas

Abstract: There is controversy over the histogenesis of Kaposi's sarcoma (KS) from lymphatic or blood vessel endothelium. D2-40 is a novel monoclonal antibody to an Mr 40,000 O-linked sialoglycoprotein that reacts with a fixation-resistant epitope on lymphatic endothelium. We sought to establish the selectivity of D2-40 for lymphatic endothelium in normal tissues and compare its reactivity with the expression of the widely used vascular endothelial marker CD31 in a series of 62 formalin-fixed and paraffin-embedded vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
423
7
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 548 publications
(460 citation statements)
references
References 17 publications
25
423
7
5
Order By: Relevance
“…In the last few years, however, a selective lymphatic marker has emerged to improve lymphatic identification significantly. 16 It is a monoclonal antibody, D 2-40, which reacts to an Mv 40 000 O-linked sialoglycoprotein on lymphatic endothelium. Additionally, it is suitable for fixed tissue specimens without epitope retrieval thus permitting far better preservation of cellular architecture.…”
Section: Gene Expression Profile Analysismentioning
confidence: 99%
“…In the last few years, however, a selective lymphatic marker has emerged to improve lymphatic identification significantly. 16 It is a monoclonal antibody, D 2-40, which reacts to an Mv 40 000 O-linked sialoglycoprotein on lymphatic endothelium. Additionally, it is suitable for fixed tissue specimens without epitope retrieval thus permitting far better preservation of cellular architecture.…”
Section: Gene Expression Profile Analysismentioning
confidence: 99%
“…5,19 D2-40, which also exhibits different reactivity in these two lesions, thus, can be used as an additional or alternative diagnostic marker. Kaposiform hemangioendothelioma is the fifth known vascular lesion that is reportedly positive for D2-40: previously the immunopositivity was shown in lymphatic malformation (lymphangioma), Kaposi sarcoma, angiosarcoma, 13 and hobnail hemangioma. 14 It has been suggested that D2-40 immunoreactivity in these neoplasms denotes a lymphothelial origin.…”
Section: D2-40 In Kaposiform Hemangioendotheliomamentioning
confidence: 99%
“…12 It has been observed that D2-40 selectively stains lymphatic endothelium in adult human tissue; this observation has been extended to finding D2-40 positivity in 'lymphangioma', Kaposi sarcoma and a subset of angiosarcoma, but not in benign tumors of blood vessels. 13 Recently, D2-40 immunopositivity was reported in hobnail hemangioma, suggesting that this tumor is of lymphatic origin. 14 Several studies employed D2-40 to evaluate lymphatics in nonvascular neoplastic and nonneoplastic lesions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…D2-40 is selective for lymphatic endothelia and has been shown to react with Kaposi's sarcoma, lymphangioma and Dabska tumor. 29,30 Membranous staining of D2-40 has been described in 51 of 53 (96%) 23 and 29 of 40 (72%) malignant mesotheliomas. 24 No single antibody has demonstrated entire sensitivity or specificity for malignant mesothelioma, 5,22,23,[31][32][33][34] and an exact description of expression frequency in areas with sarcomatoid differentiation in sarcomatoid malignant mesothelioma or biphasic malignant mesothelioma has been largely neglected.…”
mentioning
confidence: 99%